PERAN GURU PEMBIMBING DALAM PENGEMBANGAN SELF-REGULATED LEARNING - Nur Wangid, Muhammad (Jurnal Cakrawala Pendidikan, 2016)
something completed skill to self-regulate one's __A ,... today should possess as well as learners' academic achievement in the classroom _.... ,...... _'... __ learning to take place in the current school classroom such as the learners and as learning tasks, resources, and equipment have to A lot of effort must be made to r'lO'TOrrl.'S"'\ learning in a self-regulated way. The role developing that skill in students, especially """..... '-&"" .................. service, is worth exploring.